Penerapan Teknologi Mortar Busa sebagai Solusi Penggantian Jembatan Tanpa Jalur Alternatif (Studi Kasus: Penggantian Jembatan pada Ruas Tj. Redeb – Batas Bulungan) - Prabowo, Sigit Herananda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Application of foam mortar technology for bridge approach construction in the Bridge Replacement project Tj. Redeb - Bts. Bulungan provided significant cost efficiency. With the construction method half of the old bridge section remained in use for traffic lanes, while the other half was dismantled and rebuilt using foam mortar. After the foam mortar reached sufficient strength in 14 days, traffic could be diverted to the new bridge, so the remaining half of the bridge could be demolished and rebuilt using the same method, eliminating the need for temporary bridge construction and relocation of affected buildings, which are generally costly. Analyses showed that construction using foam mortar could save up to 10.77% over the conventional preferred backfill method, reducing total expenditure from IDR 7.3 billion to approximately IDR 6.59 billion. Additional benefits include a reduction in the need for retaining walls and an accelerated implementation time, thanks to its self-compacting properties and rapid hardening in 14 days.